Examining Entrepreneurial Orientation and Organizational Resilience in Small Agricultural Enterprises: Evidence from Davao Oriental - Armingol, Mike Kiven; Sagarino, Emma (Journal of Interdisciplinary Perspectives, 2025)
Small agricultural enterprises play a pivotal role in the local economy. The study aimed to investigate the impact of entrepreneurial orientation and organizational resilience on the performance of small agricultural enterprises in Davao Oriental. The study employed a quantitative descriptive-correlational design. There were 150 respondents, comprising top and middle management, as well as finance staff, who were identified through purposive quota sampling. Statistical tools, including the mean, Standard Deviation, Pearson's r, and Multiple Regression, were used to analyze the study results. Results have shown that the level of organizational performance was 4.15, which is interpreted as high. This indicates that small agricultural enterprises have demonstrated efficiency in resource management, achieving profitability while meeting operational and financial objectives. Additionally, the status of entrepreneurial orientation among small agricultural enterprises in Davao Oriental was 4.03, indicating a high level, which is often observed. The high result of entrepreneurial orientation revealed that small agricultural enterprises are likely to achieve greater capacity for innovation, faster adaptation to market changes, enhanced competitive advantage, and sustained business growth. Moreover, the enterprises’ organizational resilience was 4.16, also described as high, which is perceived to be evident. This implies that small agricultural enterprises can adapt and recover from adversities. Organizational resilience has a significant influence on organizational performance (p < .05). Regression analysis revealed that the combined influence of entrepreneurial orientation and organizational resilience explains 23.4% of the variance in organizational performance. Furthermore, future researchers may consider examining relevant business studies to investigate how entrepreneurial orientation influences other organizational variables.